119k views
3 votes
I'm stuck on this question, any ideas? thanks

I'm stuck on this question, any ideas? thanks-example-1
User Notuo
by
5.2k points

2 Answers

3 votes

Answer:

-1/36

Explanation:

lim(x→0) [1/(6 + x) − 1/6] / x

The common denominator of the two fraction in the numerator is 6(6 + x) = 36 + 6x.

lim(x→0) [6/(36 + 6x) − (6 + x)/(36 + 6x)] / x

Combine the fractions.

lim(x→0) [(6 − 6 − x) / (36 + 6x)] / x

Simplify.

lim(x→0) [-x / (36 + 6x)] / x

Divide.

lim(x→0) -1 / (36 + 6x)

Evaluate.

-1/36

User Candino
by
5.7k points
7 votes

Answer:


\lim_(x \to 0) ((1)/(6+x)-(1)/(6))/(x)=-1/36

Explanation:

So we have the limit:


\lim_(x \to 0) ((1)/(6+x)-(1)/(6))/(x)

Let's remove the fractions in the denominator by multiplying both layers by (6+x)(6). So:


\lim_(x \to 0) ((1)/(6+x)-(1)/(6))/(x)\cdot (((6+x)(6))/((6+x)(6)))

Distribute:


=\lim_(x \to 0) ((6)-(6+x))/(x(6+x)(6))

Simplify the numerator:


=\lim_(x \to 0) (6-6-x)/(x(6+x)(6))\\=\lim_(x \to 0) (-x)/(x(6+x)(6))

Both the numerator and the denominator have an x. Cancel:


=\lim_(x \to 0) (-1)/((6+x)(6))

Direct substitution:


= (-1)/((6+0)(6))

Simplify:


=-1/36

And that's our answer.

And we're done!

User Humblelistener
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.